Masterlines: The Challenge for Professional Development - Velle, Linda La; Sutton, Carole; Stenhouse, Elizabeth (Journal of Interdisciplinary Studies in Education, 2018)
Typical characteristics of Master’s-level education usefully complement the development of professional attributes leading to improved outcomes for those professions. These include critical reflection on one’s own practice, scholarship and research, and also that of others. This requires access to and engagement with a well organised and verified corpus of research-based evidence to support improved practice and scholarship. Taking an interdisciplinary approach from the viewpoints of the teaching and midwifery professions, we argue that access to well-designed Master’s-level curricula should form the basis of initial and continuing professional development for all professional practitioners, and that these curricula should be informed by research and linked directly to practice. Additionally, we propose that information and communications technologies, including social media, should better be used to facilitate access to both Master’s-level education and its underpinning evidence bases, thereby enabling continuous updating and enhancement activities to be accessible to busy professionals. If these three recommendations were to be adopted, we are convinced there would be value for the professionals themselves and, in turn, for the people they serve.